Apex to Base Left Ventricular Twist Mechanics Computed From High Frame Rate Two-Dimensional and Three-Dimensional Echocardiography: A Comparison Study - Ashraf, Muhammad (2011)
BACKGROUND: The aim of this study was to compare two-dimensional (2D) and three-dimensional (3D) methods for computing left ventricular (LV) rotation. METHODS: A two-axis linear/rotary system was designed using rotary motors controlled through a digital interface, and 10 freshly harvested pig hearts were studied. Each heart was mounted on the rotary actuator with the base being rotated at different known degrees of rotation (10°, 15°, 20°, and 25°) and was passively driven by a pump with calibrated stoke volume (50 mL) at a constant rate (60 beats/min) simultaneously. Cardiac motion was scanned to acquire 2D short-axis views using a GE Vivid 7 system for assessing rotation, and 3D apical full-volume loops were acquired using a Toshiba Applio Artida ultrasound system. Full-volume 3D image loops were analyzed online with Toshiba Wall Motion Tracking software, and short-axis 2D images were analyzed offline for LV rotation in GE EchoPAC PC at corresponding LV levels. RESULTS: At each state, both 2D and 3D echocardiography detected the changes in LV rotation but overestimated the rotation degrees. The biases for overestimation from 3D imaging were smaller compared with 2D imaging at each LV level. Both methods, when compared with each other, showed a linear correlation (r = 0.84, P < .0001). Bland-Altman comparison showed 99% of data points within range, with a constant bias between both methods (adjusted values of 3D = 1.892 + 0.964 × 3D). CONCLUSIONS: Although 3D echocardiography showed smaller bias, the results between 2D and 3D echocardiography were comparable.